Positive electrode slurry preparation method, positive electrode slurry, battery positive electrode and lithium battery
By mixing the lithium-rich manganese oxide positive electrode material with phosphoric acid and phosphate esters to form a positive electrode slurry with a pH value of 7.5-8.0, the problem of corrosion of the lithium-rich manganese-based positive electrode slurry on the current collector is solved, and the stability of the battery is significantly improved and cyclic performance.
Patent Information
- Application Number
- CN202411703126.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-21
AI Technical Summary
The lithium-rich manganese-based positive electrode slurry contains a large amount of alkaline impurities, which leads to a high pH, reacts with the current collector, introduces impurities, affecting the rate performance and circulation performance of the battery.
By mixing lithium-rich manganese oxide positive electrode material, conductive agent, dispersant, binder, phosphoric acid and phosphate esters, a positive electrode slurry is formed, and its pH value is controlled to be between 7.5 and 8.0 to inhibit corrosion of the current collector.
Effectively reduce the pH value of the positive electrode slurry, inhibit corrosion to the current collector, thereby improving the stability and circulation performance of the battery. Through the synergistic effect of phosphate ester and phosphoric acid, the stability and electrical power of the positive electrode slurry are further improved. performance.
Smart Images

Figure CN119495734A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of positive electrode slurry, and in particular to a positive electrode slurry preparation method, positive electrode slurry, a battery positive electrode and a lithium battery. Background Art
[0002] The lithium-rich manganese-based positive electrode slurry has a high pH value because it contains a large amount of alkaline impurities. When it is coated on the current collector (aluminum foil), it will react with the current collector and then introduce impurities, affecting the battery's rate performance and cycle performance. Summary of the invention
[0003] Based on this, it is necessary to provide a positive electrode slurry preparation method, positive electrode slurry, battery positive electrode and lithium battery to address the problem that lithium-rich manganese-based positive electrode slurry is easy to corrode the current collector, resulting in reduced battery rate performance and cycle performance.
[0004] The technical solution provided by the present invention is: A method for preparing a positive electrode slurry, comprising: Mixing a lithium-rich manganese oxide positive electrode material, a conductive agent, a dispersant, a binder, phosphoric acid and a phosphate ester to form a positive electrode slurry; Wherein, the pH of the positive electrode slurry is 7.5-8.0.
[0005] The phosphate ester of the present invention is trimethyl phosphate or triethyl phosphate.
[0006] The mass of the phosphate ester of the present invention is 30%-70% of the mass of phosphoric acid.
[0007] The total mass of the lithium-rich manganese oxide positive electrode material, the conductive agent, the dispersant and the binder of the present invention is m 1. The total mass of phosphoric acid and phosphate ester is m 2, m 2 for m 1%-2% of 1.
[0008] The binder of the present invention is polyacrylic acid.
[0009] The conductive agent of the present invention is one of graphite, carbon black, VGCF and CNT or a mixture of several thereof, and the dispersant is one of sodium carboxymethyl cellulose and sodium alginate or a mixture of two thereof.
[0010] A positive electrode slurry is prepared by adopting the positive electrode slurry preparation method.
[0011] A battery positive electrode is obtained by coating the positive electrode slurry on a current collector and then drying it.
[0012] The coating load of the positive electrode slurry on the current collector is not less than 10 mg / cm 2 .
[0013] A lithium battery comprises the battery positive electrode.
[0014] The beneficial effects of the present invention include at least one of the following: Phosphoric acid and phosphate esters can reduce the pH value of the positive electrode slurry and maintain it in a weakly alkaline state, thereby inhibiting the corrosion of the positive electrode slurry to the current collector, thereby improving the stability and cycle performance of the battery. Phosphate esters can produce a good synergistic effect with phosphoric acid. In addition to reducing the pH value of the positive electrode slurry, they also improve the stability of the positive electrode slurry through other mechanisms to ensure the improvement of the battery's electrical performance. Phosphate esters and phosphoric acid can improve the surface morphology and peeling force of the battery positive electrode prepared with aqueous positive electrode slurry, and effectively increase the coating load of aqueous positive electrode slurry, so that the mechanical properties and electrical properties of the aqueous slurry can be better than those of the oil-based slurry, thereby reducing the use of oil-based slurry. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 The magnification test diagrams of Example 1 of the present invention, Comparative Example d2 and Comparative Example e1; Figure 2 The cycle test diagrams of Example 1 of the present invention, Comparative Example d2 and Comparative Example e1; Figure 3 The photographs are of the positive electrode surfaces of the batteries of Example 1 of the present invention, Comparative Example d1, Comparative Example d2 and Comparative Example e1. DETAILED DESCRIPTION
[0015] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0016] Embodiment 1: This embodiment provides a positive electrode slurry, and the preparation method thereof comprises the following steps: Step S1: Add a dispersant into deionized water, stir at 2000 rpm for 4h-6h to form a dispersant colloid, then add a conductive agent into the dispersant colloid, stir at 2000 rpm for 2h to form a conductive colloid.
[0017] The dispersant is sodium carboxymethyl cellulose (CMC), or sodium alginate, or a mixture of sodium carboxymethyl cellulose and sodium alginate. In this embodiment, the dispersant is sodium carboxymethyl cellulose (CMC).
[0018] The conductive agent is one of graphite, carbon black (SP), VGCF and CNT, or a mixture of several thereof. In this embodiment, the conductive agent is carbon black (SP).
[0019] Step S2: Li-rich manganese oxide positive electrode material (LRMO, chemical formula Li 1.2 Ni 0.133 Co 0.133 Mn 0.533 ) was added to the conductive glue solution and stirred at 3000 rpm for 2 hours to form the first positive electrode slurry precursor solution.
[0020] Step S3: Add the binder to the first cathode slurry precursor solution and stir at 2500 rpm for 0.5 h to form a second cathode slurry precursor solution.
[0021] In this embodiment, the binder is polyacrylic acid (PAA).
[0022] Step S4: Add phosphoric acid to the second positive electrode slurry precursor solution and stir at 2000 rpm for 0.5 h to adjust the pH to 8.5-9.0 to form a third positive electrode slurry precursor solution, and add deionized water to the third positive electrode slurry precursor solution to adjust the viscosity of the third positive electrode slurry precursor solution to 4000 mPa·s-8000 mPa·s.
[0023] Step S5: adding phosphate to the third cathode slurry precursor solution and stirring at 2000 rpm for 20 min until the pH is in the range of 7.5-8.0, thereby obtaining cathode slurry. The phosphate ester may be trimethyl phosphate, triethyl phosphate, or a mixture of trimethyl phosphate and triethyl phosphate. In this embodiment, the phosphate ester is specifically trimethyl phosphate.
[0024] The mass ratios of LRMO, SP, CMC and PAA are 95:2:1:2, respectively, where the total mass of LRMO, SP, CMC and PAA is m 1. The mass of phosphoric acid is 1% m 1. The mass of phosphate ester is 0.5% m 1.
[0025] The positive electrode slurry is coated on the current collector (aluminum foil) with a coating load of 10 mg / cm 2 , and baked at 80°C for 2 h and vacuum baked at 110°C for 12 h to obtain the battery positive electrode.
[0026] Assemble the positive terminal of the battery into a button cell.
[0027] Among them, the battery positive electrode is subjected to a peeling force test, and the peeling strength is measured according to the 180° peeling force test standard. The battery positive electrode is cut into a rectangle with a length of 100mm and a width of 25mm. Take a stainless steel plate with a width of 50mm, stick a double-sided tape (length 10mm, width 25mm), paste the cut battery positive electrode on the double-sided tape on the stainless steel plate, use a 2Kg roller to roll back and forth on the surface of the positive electrode sheet 3 times, and then fix the sample on the testing machine. The axial direction of the electrode sheet is consistent with the direction of force application, and the average peeling force (unit N / m) is recorded.
[0028] Carry out rate performance test and cycle performance test on button batteries.
[0029] The rate performance test process is as follows: in a constant temperature box at 25°C, the button battery is charged with constant current and constant voltage in the voltage range of 2.0V-4.7V at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and 0.1C in sequence (up to the rate of 0.02C) and discharged with constant current. Each rate is cycled three times and the battery discharge data is recorded. The cycle performance test process is as follows: in a constant temperature box at 25°C, the button battery cell is charged to 4.7V (end rate 0.02C) at 1C constant current and constant voltage, and then discharged to 2.0V at 1C constant current. The charge and discharge cycle is repeated in this way, and the capacity retention rate of the battery after 100 cycles is recorded.
[0030] Comparative Example a1: The difference between this comparative example and Example 1 is that the mass of phosphoric acid is 0.5% m 1, and step S5 is omitted, the third positive electrode slurry precursor solution is directly used as the positive electrode slurry, and no phosphate is added.
[0031] Comparative Example a2: The difference between this comparative example and comparative example a1 is that the mass of phosphoric acid is 1% m 1.
[0032] Comparative Example a3: The difference between this comparative example and comparative example a1 is that the mass of phosphoric acid is 1.5% m 1.
[0033] Comparative Example b1: The difference between this comparative example and comparative example a3 is that phosphoric acid is replaced by oxalic acid.
[0034] Comparative Example b2: The difference between this comparative example and comparative example b1 is that the mass of oxalic acid is 2%. m 1.
[0035] Comparative Example b3: The difference between this comparative example and Example 1 is that phosphoric acid is replaced by oxalic acid, and the mass of oxalic acid is 1.5%. m 1.
[0036] Comparative Example c1: The difference between this comparative example and comparative example a1 is that phosphoric acid is replaced by citric acid, and the mass of citric acid is 2.3%. m 1.
[0037] Comparative Example c2: The difference between this comparative example and Example 1 is that phosphoric acid is replaced by citric acid, and the mass of citric acid is 2.3%. m 1.
[0038] For ease of viewing, the specific differences between Example 1, Comparative Examples a1-a3, Comparative Examples b1-b3, Comparative Example c1 and Comparative Example c2 are shown in Table 1.
[0039] Table 1
[0040] Comparative Example d1: The difference between this comparative example and Example 1 is that step S4 and step S5 are omitted, and the second positive electrode slurry precursor solution is directly used as the positive electrode slurry without adding phosphoric acid and phosphate ester.
[0041] Comparative Example d2: The difference between this comparative example and comparative example d1 is that the coating loading of the positive electrode slurry on the current collector is 3 mg / cm 2 .
[0042] Comparative Example e1: This comparative example provides a positive electrode slurry, which is obtained by mixing 95 parts of LRMO, 2 parts of SP and 3 parts of polyvinylidene fluoride (PVDF) by weight. The positive electrode slurry is coated on the current collector with a coating load of 10 mg / cm 2 .
[0043] The peeling force test data of all the above embodiments and comparative embodiments are shown in Table 2.
[0044] Table 2
[0045] By comparing Comparative Example d1, Comparative Example a1-Comparative Example a3, as the pH of the positive electrode slurry gradually decreases from strong alkalinity to weak alkalinity, the surface state of the positive electrode of the battery gradually improves, and the peeling force gradually increases. The reason is probably due to the decrease in pH, which inhibits the corrosion of the positive electrode slurry to the current collector. However, when the pH of the positive electrode slurry is too low and tends to be neutral, it will reduce the stability of the dispersant and have an adverse effect on the peeling force. Similar conclusions can also be obtained by comparing Comparative Example d1, Comparative Example b1-Comparative Example b3, and can also be obtained by Comparative Example d1, Comparative Example c1 and Comparative Example c2.
[0046] It is worth noting that the pH of the positive electrode slurry in Example 1 is between that of Comparative Example a2 and Comparative Example a3, but its peeling force is significantly better than that of Comparative Example a2 and Comparative Example a3. This indicates that in addition to protecting the positive electrode by lowering the pH, phosphate ester also has other reaction mechanisms to improve the stability of the positive electrode. For example, phosphate ester may form a protective layer on the surface of LRMO particles.
[0047] See also Figure 3 Among them, the surface morphology of the battery positive electrode in Comparative Example e1 is significantly better than that of Comparative Example d1 and Comparative Example d2. However, Example 1 uses phosphoric acid and phosphate ester to make the surface morphology of the battery positive electrode equal to that of Comparative Example e1, and the peeling force is significantly better than that of Comparative Example e1.
[0048] The rate performance and cycle performance of all the above examples and comparative examples are shown in Table 3.
[0049] Table 3
[0050] First, it can be seen that in Comparative Example d1, since no acid or phosphate was added to the positive electrode slurry, its alkalinity was too strong. 2 In this case, the battery structure cannot be effectively formed and the coating load can only be controlled at 3 mg / cm 2 .
[0051] Comparing Comparative Example d2 and Comparative Example a1-Comparative Example a3, as the pH gradually decreases, the battery rate performance first increases and then decreases, the first effect continues to improve, and the cycle capacity decreases. It is worth noting that the pH of the positive electrode slurry in Example 1 is between Comparative Example a2 and Comparative Example a3, but its first effect is significantly better than Comparative Example a3, and the cycle capacity is also better than Comparative Example d2, which means that in addition to lowering the pH of the positive electrode slurry to protect the current collector, phosphate ester also has other reaction mechanisms to improve the stability of button batteries, and this conclusion is consistent with the conclusion of the peeling force test.
[0052] Comparing Comparative Example d2, Comparative Example b1 and Comparative Example b2, as the pH gradually decreases, the battery rate performance first increases and then decreases, and the first effect first increases and then decreases, but its cycle capacity has decreased significantly. In particular, Comparative Example b3 and Comparative Example b2 are compared. When part of the oxalic acid is replaced by phosphate ester, the battery first effect and cycle capacity are improved, but its cycle capacity is still significantly lower than that of Comparative Example d2, indicating that phosphate ester is likely to form a certain protective layer on the surface of LRMO particles, but the content of the protective layer is low. This reversely proves that there is likely to be a certain synergistic effect between phosphate ester and phosphoric acid.
[0053] Similar conclusions can be obtained by comparing Comparative Example d2, Comparative Example c1 and Comparative Example c2.
[0054] In summary, Example 1 is the best example compared with Comparative Examples a1 to a3, Comparative Examples b1 to b3, Comparative Example c1, Comparative Example c2, and Comparative Example d2.
[0055] On this basis, Example 1, Comparative Example d2 and Comparative Example e1 were compared and combined Figure 1 and Figure 2 First, it can be determined that the battery performance in Comparative Example d2 is better than that in Comparative Example e1. Combined with the above-mentioned peeling force test, it can be seen that the positive electrode peeling force in Comparative Example d2 is inferior to that in Comparative Example e1. Among them, Comparative Example e1 is an oil-based slurry, and Comparative Example d2 is a water-based slurry. In other words, under normal circumstances, the mechanical properties of the water-based slurry are not as good as those of the oil-based slurry, but the electrical properties are better than those of the oil-based slurry.
[0056] However, Example 1, through the combination of phosphoric acid and phosphate ester, not only further improves the electrical performance of the battery on the basis of Comparative Example d2, making it further superior to Comparative Example e1, ensuring the electrical performance advantage of the water-based slurry over the oil-based slurry, but also enhances the coating load and peeling force of the water-based slurry, so that the mechanical properties of the water-based slurry can also be better than those of the oil-based slurry.
[0057] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0058] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a positive electrode slurry, characterized in that: include: Mixing a lithium-rich manganese oxide positive electrode material, a conductive agent, a dispersant, a binder, phosphoric acid and a phosphate ester to form a positive electrode slurry; Wherein, the pH of the positive electrode slurry is 7.5-8.
0.
2. The method for preparing positive electrode slurry according to claim 1, characterized in that: The phosphate ester is trimethyl phosphate or triethyl phosphate.
3. The method for preparing positive electrode slurry according to claim 2, characterized in that: The mass of phosphate ester is 30%-70% of the mass of phosphoric acid.
4. The method for preparing positive electrode slurry according to claim 3, characterized in that: The total mass of lithium-rich manganese oxide positive electrode material, conductive agent, dispersant and binder is m 1. The total mass of phosphoric acid and phosphate ester is m 2, m 2 for m 1%-2% of 1.
5. The method for preparing positive electrode slurry according to claim 1, characterized in that: The binder is polyacrylic acid.
6. The method for preparing positive electrode slurry according to claim 1, characterized in that: The conductive agent is one of graphite, carbon black, VGCF and CNT or a mixture of several thereof, and the dispersant is one of sodium carboxymethyl cellulose and sodium alginate or a mixture of two thereof.
7. A positive electrode slurry, characterized in that: The positive electrode slurry is prepared by the positive electrode slurry preparation method according to any one of claims 1 to 6.
8. A positive electrode of a battery, characterized in that: The method is obtained by coating the positive electrode slurry as claimed in claim 7 on a current collector and then drying the same.
9. The positive electrode of the battery according to claim 8, characterized in that: The coating loading of the positive electrode slurry on the current collector is not less than 10 mg / cm 2 .
10. A lithium battery, characterized in that: Comprising the battery positive electrode as claimed in claim 8.